Bulgarian traditional folklore celebrating food and sustainability - Bogueva, Diana; Marinova, Dora; Todorov, Vladislav (2021)
Being an integral part of the past cultural heritage, the traditional Bulgarian folklore festivals, carnivals, and celebrations are continuing to promote sustainable practices that venerate and respect nature. The article focusses specifically on celebrations related to food and plant growing. It reviews the intangible cultural heritage of the Bulgarian folklore, including traditions whose roots originated from pagan rituals but continue to be observed now. A description of the Kukeri carnival, Trifon Zarezan, Baba Marta, Peperuda (Butterfly), Rose Festival, Nestinari dancing rituals, and Enyovden are provided within a sustainability context. A common feature between these celebrations is the respect for nature and its healing capacity with people being perceived as part of the natural world. These traditional folklore festivities have survived the test of time with very little commercialisation. Food plays a major role in them, but most importantly, they help maintain the community spirit and social bonding.